The Role of Research and Development in Renewable Energy Consumption - Sustainable Human Development Nexus: Evidence from EAC Member Countries - Sheikh Ali, Ali Yassin (International Journal of Energy Economics and Policy, 2025)
The pressing challenges of climate change and energy access in the East African Community (EAC) necessitate a strategic focus on research and development (R&D) to enhance renewable energy consumption and support sustainable human development. This study investigates the critical role of research and development (R&D) in promoting renewable energy consumption and its impact on sustainable human development within the East African Community (EAC). As global climate change intensifies, the transition from conventional energy sources to renewable alternatives is essential for fostering economic growth and improving human development indicators. Despite the recognized potential of renewable energy, EAC nations face challenges, including inadequate funding for R&D, limited technological capabilities, and ineffective policy frameworks. This paper analyzes the intricate relationship between R&D investments and renewable energy adoption, utilizing a comprehensive econometric approach with data spanning from 1996 to 2021. The study employs advanced econometric estimators, including Feasible Generalized Least Squares (FGLS) and Panel-Corrected Standard Errors (PCSE), alongside robustness tests such as Driscoll-Kraay standard errors and Fully Modified Ordinary Least Squares (FMOLS). The findings reveal that enhancing R&D is vital for overcoming barriers to renewable energy implementation, ultimately contributing to sustainable development goals. The study underscores the necessity for targeted policy interventions that leverage R&D to facilitate technological advancements, improve energy efficiency, and promote equitable access to renewable energy resources in the EAC region.